Manipulating Image and Communication Issues in the Dolly Ex-Prostitution District Community Development Program - Wiyanto, Clara Carolina; Krisdinanto, Nanang (Unisba Press, 2022)
This research focuses on the problematic meaning of opinion leaders' views on the Dolly Bangkit community development program initiated by the Surabaya City Government in response to the conflict following the closure of Dolly's prostitution site in Surabaya. The problems are described from the opinion leader's point of view. This research uses a qualitative approach and phenomenological methods. The aim is to describe the experience of opinion leaders in dealing with the Dolly Bangkit program, which in turn shapes the meaning of the program. The results indicate that there are problems with the experience as well as the meaning. On the one hand, this program is interpreted as a helpful program to change the negative image of the Dolly area. On the other hand, opinion leaders also interpret this program as an imaging event by the Surabaya City Government officials to show that they are responsible for the closure. They also saw that there was a neglect of several essential things in the community development program, such as the participation or involvement of the target community and training that facilitate the target community in finding solutions, as well as aspects of equality.